Factors Influencing the Behavioural Intention to Use Cryptocurrency in Emerging Economies During the COVID-19 Pandemic: Based on Technology Acceptance Model 3, Perceived Risk, and Financial Literacy - Jariyapan, Prapatchon; Mattayaphutron, Suchira; Gillani, Syeda Noorzahrah; Shafique, Owais (Frontiers in Psychology, 2022)
Cryptocurrency can redefine the interplay of Internet-connected world markets by eliminating constraints set by traditional local currencies and exchange rates. Cryptocurrency is developing as it offers promising prospects in revolutionising digital markets through the use of duty-free trading. This study investigates the factors influences the behavioural intention to use cryptocurrency based on the Technology Acceptance Model 3 (TAM 3) during the Covid-19 (SARS-COV-2) pandemic. Data was collected through a cross-sectional questionnaire from 357 Pakistani business-educated adults including investors – who had a rudimentary understanding of the technology and financial instruments. PLS based SEM was brought to play to test the developed theoretical framework based on the Technology acceptance model 3. The PLS model explained 72.1% of the behavioural intention to use cryptocurrency. Surprisingly, risk was not a major consideration. This might be due to the fact that the majority of respondents thought working with cryptocurrency was hazardous. Willingness to handle cryptocurrency risk, on the other hand, might be a stumbling block to acceptance. The most essential aspect of a cryptocurrency's success was perceived usefulness. Moreover, the moderating role of experience was not substantiated in this study. However, perceived usefulness was identified as a partial mediator of subjective norm and perceived ease to use. This study contributed to the literature through the application of TAM 3 (an extension of the technology acceptance models) to investigate the fundamental qualities a cryptocurrency should have to influence investor’s behavioural intention to use it. The findings provide revolutionary insights for the present and future market players for investment planning and developing improved cryptocurrencies.